'Open Window': a randomized trial of the effect of new media art using a virtual window on quality of life in patients' experiencing stem cell transplantation. Issue 2 (6th December 2011) - McCabe, Catherine; Roche, Denis; Hegarty, Fran; McCann, Shaun
Abstract Objectives To measure the psychological effect of an art intervention on hospitalized patients and explore benefits to their quality of life. Methods We conducted a large prospective randomized trial between July 2006 and August 2009 of an art intervention, Open Window (OW), in patients undergoing stem cell transplantation for a hematological malignancy compared with a control group. The primary endpoint measured the effect of an art intervention on levels of anxiety, depression, and stress using the Hospital Anxiety and Depression Scale and the Distress Thermometer. The secondary endpoint measured the influence of OW on patients' experiences of stem cell transplantation using the OW survey and expectations questionnaires. Results Of the 199 patients in the study, 96 were randomized to the intervention group and 103 to the control group. Participants in the intervention group had significantly reduced levels of anxiety on the day before transplant (p = 0.001), at day 7 (p = 0.041), and day 60 (p = 0.035). There was a significant reduction in depression before transplant (p = 0.022). Participants in the intervention group reported better experiences (p < 0.005). Qualitative data showed that those in the intervention group commented freely on their likes and dislikes about OW and how it made them feel. Conclusion An art intervention, OW, had a positive influence on health‐related quality of life and patients' experiences of having a stem cell transplant. Copyright © 2011 John Wiley & Sons, Ltd.